Effective Ways of Using Water with Information Systems - Sultonov Akmal Obidovich (International Journal on Economics, Finance and Sustainable Development, 2021)
The article discusses complex ways of optimal use of water resources, depending on indicators of efficiency in agriculture. The main aspects of the structure of the information system of water use in agriculture are analyzed and systematic conclusions are drawn about the extent to which it is possible to achieve strategic goals.